Peranan Retorika Dalam Pengembangan Dakwah - Mukroni AB.; Mujiono (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2022)
Da'wah is the responsibility of every individual Muslim to appeal to the community using effective means and media. This essay aims to provide light on the function of rhetoric in the evolution of da'wah. The approach employed is a review of the literature (library research). This article reinforces the notion that the usage of da'wah media varies by community. Several variables impact the disparity in knowledge levels, including social, cultural, and environmental influences. Rhetoric, as a practical science for influencing others via spoken words, either verbally or in writing, may be utilized to help the missionary mission successful.